PENERAPAN MEMBACA KRITIS PADA TEKS EDITORIAL UNTUK MENGOPTIMALKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Pardede, Oktaviandi Bertua (Fakultas Bahasa dan Seni, 2024)
Thinking creatively through critical reading of editorial texts means that the dimensions of students' creative thinking can be optimized according to their scientific field. So this research aims to focus on the extent of student creativity in creative thinking activities through the critical reading they experience on the object of reading scientific articles. This research also measures the increase in students' creative thinking abilities through lecture activities carried out in groups. To know the contribution of critical reading activities in the affectivity aspect. This research carried out at the Faculty of Teacher Training and Education Unpri, applies quantitative and qualitative research approaches, namely assessing learning outcomes and measuring student learning activities. The research method used is action research using the John Elliot model. Then the research sample was determined using purposive sampling with a total of 40 students. This research resulted in the conclusion that the application of critical reading and creative thinking abilities increased linearly with each increase between cycles, namely 22% to 6% and 25% to 10%. The final scores for critical reading and creative thinking skills were obtained at 80.5 and 80.725 respectively. This shows that increasing critical reading and creative thinking has an impact on student learning activities that become more meaningful and contribute to contextual learning. Keywords: Creative thinking, critical reading, scientific articles, CAR